Analisis Transparansi dan Akuntabilitas Alokasi Dana Desa (ADD) Di Desa Tangai Kecamatan Rambang Kuang - Sari Pebriyanti; Totok Sudiyanto; Emilda Emilda (Jurnal Media Akuntansi (Mediasi), 2021)
ABSTRACT This study aims to determine the Transparency and Accountability of Village Fund Alloction (ADD) in Tangai Village, Rambang Kuang District, Ogan ilir Regency, 2017-2019. The method used in this study is a qualitative method, the sample in this study is in the form of planning and accountability for the 2017-2019 period, the data sources in this study are primary and secondary data, data collection techniques used are interview and documentation techniques, data analysis techniques used is a qualitative descriptive analysis. The results of the transparency and accountability research on the allocation pf village funds in Tangai Village in 2017-2019 at the planning stage, community participation is still low in participating in deliberations which reflects the lack of awareness and awareness of the community to play an active role in village development. The reporting/ accountability stage that was conveyed by the village head to the Sub-District Head was in accordance with Minister of Home Affairs Regulation No. 20 of 2018, this can be seen with an explanation of the use village funds, but it was not yet supported with expenditure documents such as memorandum, receipts and invoices. Keyword: Transparency, Accountability of Village Fund Allocation (ADD)  ABSTRAK Penelitian ini bertujuan untuk mengetahui Transparansi dan Akuntabilitas Alokasi Dana Desa (ADD) Di Desa Tangai Kecamatan Rambang Kuang Kabupaten Ogan Ilir Tahun 2017-2019. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, sampel dalam penelitian ini berupa perencanaan dan pertanggungjawaban periode 2017-2019, sumber data dalam penelitian ini adalah data primer dan sekunder, teknik pengumpulan data yang digunakan adalah teknik wawancara dan dokumentasi, teknik analisis data yang digunakan adalah analisis deskriptif kualitatif. Hasil penelitian transparansi dan akuntabilitas alokasi dana desa di Desa Tangai tahun 2017-2019 pada tahap perencanaan, partisipasi masyarakat masih rendah dalam mengikuti musyawarah yang mencerminkan kurangnya tingkat kepedulian dan kesadaran masyarakat untuk berperan aktif dalam pembangunan desa. Tahap pelaporan/pertanggungjawaban yang telah di sampaikan Kepala Desa ke Camat telah sesuai permendagri no 20 tahun 2018 hal ini dapat dilihat dengan adanya penjelasan penggunaan dana desa, tetapi masih belum di dukung dengan dokumen-dokumen pengeluaran seperti nota, kwitansi, dan faktur. Kata Kunci: Transparansi, Akuntabilitas Alokasi Dana Desa (ADD)